Pharmacological treatments of fibromyalgia in adults; overview of phase IV clinical trials - Alorfi, Nasser M. (Frontiers in Pharmacology, 2022)
Abstract: Background: Fibromyalgia is a chronic neurological condition characterized by a wide spread of pain. The effectiveness of current pharmacological treatments is limited. However, several medications were approved for phase IV to evaluate the drugs used. Aim: To identify the drugs used in phase IV of completed clinical trials for fibromyalgia management in adults, primary endpoints, and treatment outcomes. Method: Analysis of eligible trials registered at ClinicalTrials.gov for phase IV only which were publicly available. Uses of the drugs in FB were reviewed. Results: As of August 8th, 2022, a total of 1263 phase IV clinical trials were identified. Only 121 were used for fibromyalgia. Of them, 10 clinical trials were eligible for the current study. Drugs used in phase IV are milnacipran, duloxetine, pregabalin, a combination of tramadol and acetaminophen, and armodafinil. The effectiveness of current pharmacological treatments is apparently limited. Conclusion: Due to its complexity with other pain types, treatment options for only fibromyalgia were limited and designed to alleviate the consequences rather than the pathological pathway of the condition itself. Pain management specialists have numerous pharmacologic options available to manage fibromyalgia. Keywords: Fibromyalgia; pain; clinical trials; neuroscience; phase IV.